Characterization of lithium-batteries for high power applications. (June 2022) - Bandini, Gabriele; Caposciutti, Gianluca; Marracci, Mirko; Buffi, Alice; Tellini, Bernardo
Abstract: Lithium batteries feature high energy density and long service life, and those find wide use in energy storage systems, portable electronics, and electric vehicles. Lithium batteries are commonly classified as energy-oriented devices, while their use for high-power applications is limited due to technical concerns regarding thermal management and reduced life. On the other hand, the development of Lithium batteries for both high-power and high-energy can lead to the development of more compact electrical devices, including pulsed power operating systems, and the increase of electric vehicle performance. In the current work, we propose and assess a method to operate commercial 3 Ah 18, 650 Li-Ion cells based on LiNiCOMnO2 technology as power-oriented devices. The adopted operating conditions are significantly beyond the manufacturer specifications. We thus implemented a novel internal resistance monitoring strategy to limit the battery aging, keeping the cell temperatures under control. The pursued approach extended the Lithium battery operation range towards high specific power with minor impact on the state of health of the cells and on the total delivered energy. Highlights: A method based on internal resistance monitoring is used for battery aging control. Lithium batteries are used for high power applications. New operating area of lithium batteries is explored in the Ragone plot. The batteries are tested well beyond the manufacturer specification.